Avaliação da contaminação da câmara anterior na cirurgia de facoemulsificação com implante de lente intra-ocular - Shiratori, Cesar Nobuo [UNESP]; Schellini, Silvana Artioli [UNESP]; Rodrigues, Antonio Carlos [UNESP]; Correa, Carlos Roberto [UNESP] (My University, 2002)
Purpose: To evaluate the frequency of anterior chamber contamination during phacoemulsification surgery with intraocular lens implant. Method: A prospective study was done with 30 patients submitted to phacoemulsification surgery with intraocular lens implant. Two samples of the aqueous humor were removed from the anterior chamber, one at the beginning and another one at the end of the surgery and were inoculated in culture plates for anaerobic and aerobic bacteria and fungi. Results: Intraocular aspirates yielded negative cultures. Conclusion: The absence of microorganisms in the samples evaluated allowed us to conclude that contamination during the phacoemulsification surgery with lens implant is unusual.
Anterior chamber contamination in phacoemulsification surgery with intraocular lensimplant
Keywords: Aqueous humor; Cataract extraction; Cell culture; Contamination; Phacoemulsification